ETNOFARMASI DAN INVENTARISASI TANAMAN OBAT ASAL DESA LEMBANNA KEC.BONTOBAHARI KAB.BULUKUMBA PROPINSI SULAWESI SELATAN - Hasnaeni Hasnaeni (As-Syifaa Jurnal Farmasi, 2010)
Etnofarmacy is the study of how an ethnic community or region in the use of a medicinal plant. Observed result obtained from the inventory data  that is there are several types of plant used by communities in rural Lembanna in the treatment of various diseases of Guajava (Psidium guajava), Papaya (Carica papaya), Mustache cat (Ortoshipon stamineus), Carambola (Averhoa blimbi), Princess shame (Mimosa pudica), Loranthus (Helianthus annus), Chili (Capsicum annum), Noni (Morinda citrifolia), Distance experts (Jatropa carpus), Sirih (Piper betle).Keyword : Etnofarmacy